Factors affecting the accuracy of endoscopic transpapillary sampling methods for bile duct cancer. Issue 2 (5th July 2013) - Nishikawa, Takao; Tsuyuguchi, Toshio; Sakai, Yuji; Sugiyama, Harutoshi; Tawada, Katsunobu; Mikata, Rintaro; Tada, Motohisa; Ishihara, Takeshi; Miyazaki, Masaru; Yokosuka, Osamu
<x xml:space="preserve">Abstract</x> Background and Aim Various methods for endoscopic transpapillary sampling have been developed. However, the factors affecting the accuracy of these methods for bile duct cancer are unknown. The aim of the present study was to determine the factors affecting the accuracy of endoscopic transpapillary sampling methods. Methods We reviewed the results from 101 patients with bile duct cancer who underwent transpapillary sampling by aspiration bile cytology, brushing cytology, and fluoroscopic forceps biopsy. The final diagnosis of bile duct cancer was made on the basis of pathological evaluation of specimens obtained at surgery and the clinical course over at least 1 year in patients not operated on. We carried out subgroup analyses for the factors affecting the accuracy of each transpapillary sampling method. Results Aspiration bile cytology was carried out 238 times in 77 patients, brushing cytology was carried out 67 times in 60patients, and fluoroscopic forceps biopsy was carried out 64 times in 53 patients. Accuracies of aspiration bile cytology were significantly higher for longer (≥15 mm) biliary cancerous lesions than for shorter (<15 mm) lesions (30% vs 18%, respectively, P = 0.049). Accuracies of brushing cytology and fluoroscopic forceps biopsy were significantly higher for non‐flat than for flat‐type biliary cancerous lesions (brushing: 58% vs 38%, respectively, P = 0.032; forceps biopsy: 60% vs 33%, respectively, P = 0.043). Conclusion Endoscopic transpapillary sampling methods are more accurate for longer or elevated (non‐flat) biliary cancerous lesions than for shorter or flat lesions.